Differential effects of the tricyclic antidepressant amoxapine on glycine uptake mediated by the recombinant GLYT1 and GLYT2 glycine transporters - Núñez, Enrique (2000)
1. We examined the effects of nine different tricyclic antidepressant drugs on the glycine uptake mediated by the glycine transporter 1b (GLYT1b) and glycine transporter 2a (GLYT2a) stably expressed in human embryonic kidney 293 cells. Desipramine, imipramine, clomipramine, nomifensine and mianserin had no effect on the activity of the glycine transporters. Doxepin, amitriptyline and nortriptyline inhibited the two transporter subtypes to a similar extent. 2. Amoxapine displayed a selective inhibition of GLYT2a behaving as a 10 fold more efficient inhibitor of this isoform than of GLYT1b. 3. Kinetic analysis of the initial rates of glycine uptake by GLYT2a as a function of either glycine, chloride or sodium concentration, in the absence and presence of amoxapine indicated that amoxapine behaved as a competitive inhibitor of both glycine and chloride and a mixed-type inhibitor with respect to sodium. 4. A kinetic model was developed which explains adequately these data, and gives information about the order of binding of sodium and chloride ions to GLYT2a. 5. Our results may contribute to the development of the glycine transporter pharmacology. Additionally, the inhibition of the glycine uptake by GLYT2 is suggested to have some role in the sedative and psychomotor side effects of amoxapine.